2015
DOI: 10.1002/atr.1323
|View full text |Cite
|
Sign up to set email alerts
|

Human‐centered designs, characteristics of urban streets, and pedestrian perceptions

Abstract: SUMMARYThis paper presents the results of a study conducted to examine the characteristics of human-centered design and pedestrians' perceptions of street design features. The main emphasis was to determine the existence of empirical evidence that human-centered design increases pedestrian satisfaction levels and enhances community walkability. The following approach was applied in the study: (i) the existing research concerning walkable community and pedestrian facility designs was reviewed; (ii) survey data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 20 publications
1
16
0
1
Order By: Relevance
“…); (d) safety of the walking environment; (e) interesting and aesthetically appealing context or environment around the walking paths; and (f) well-connected network of walking paths, both within and beyond the community. Choi, Kim, Min, Lee, and Kim (2016) call the set of such characteristics "human-centered street design" (Choi et al, 2016, p. 120). Using a measure of pedestrian perceptions, these authors identified the following human-centered design elements as most significant for pedestrian satisfaction: streets with fewer vehicle lanes, presence of crosswalks, a small number of bus stops and driveways to obstruct pedestrian traffic, wider sidewalks, strategically placed planting strips, and commercial areas with easy access to pedestrians and people using public transit (Choi et al, 2016).…”
Section: Built Environment and Walkabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…); (d) safety of the walking environment; (e) interesting and aesthetically appealing context or environment around the walking paths; and (f) well-connected network of walking paths, both within and beyond the community. Choi, Kim, Min, Lee, and Kim (2016) call the set of such characteristics "human-centered street design" (Choi et al, 2016, p. 120). Using a measure of pedestrian perceptions, these authors identified the following human-centered design elements as most significant for pedestrian satisfaction: streets with fewer vehicle lanes, presence of crosswalks, a small number of bus stops and driveways to obstruct pedestrian traffic, wider sidewalks, strategically placed planting strips, and commercial areas with easy access to pedestrians and people using public transit (Choi et al, 2016).…”
Section: Built Environment and Walkabilitymentioning
confidence: 99%
“…Choi, Kim, Min, Lee, and Kim (2016) call the set of such characteristics "human-centered street design" (Choi et al, 2016, p. 120). Using a measure of pedestrian perceptions, these authors identified the following human-centered design elements as most significant for pedestrian satisfaction: streets with fewer vehicle lanes, presence of crosswalks, a small number of bus stops and driveways to obstruct pedestrian traffic, wider sidewalks, strategically placed planting strips, and commercial areas with easy access to pedestrians and people using public transit (Choi et al, 2016). Other studies, however, have not been so equivocal in their determination of "pedestrian-friendly" characteristics of streets and neighborhoods.…”
Section: Built Environment and Walkabilitymentioning
confidence: 99%
“…adequate seating and smooth pavements) may encourage a person's decision to go out and be more social, depending on their sense of safety. Other studies demonstrated that people recognized strip planting within green urban infrastructures, as the most relevant design component that could enhance satisfaction levels and increase willingness to walk, while the existence of driveways and the number of vehicle lanes as a design element, reduces their satisfaction [14]. Therefore, a good and accessible universal design approach in pedestrian infrastructures and modal interfaces is essential to encourage elderly people, and people with disabilities, to be more social and go out more, which may in turn enhance their security and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…This increase of computational technologies into modern smart cities where automated infrastructures interact with the urban citizens [3] makes it feasible to collect passenger trip information in advance using a booking or reservation system provided through a mobile application or station kiosks. In combination with real-time multi-sensor origin-destination (OD) trip estimation techniques [4,5], accurate real-time vehicle scheduling is possible.As average trip distances grow, cities are forced to dedicate more land to roads, driveways, and parking structures, making pedestrian and bicycle travel less attractive and more dangerous [6]. Autonomous vehicles may be a solution to this problem with their claims to improved operational performance.…”
mentioning
confidence: 99%